Akulturasi Budaya Bakar Tongkang di Masyarakat Kabupaten Rokan Hilir - Mutiara Tanila; Jeri Candra; Masyhuri M (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the process of cultural acculturation in the Bakar Tongkang tradition in Rokan Hilir Regency and its role in strengthening social cohesion within a multicultural society. The research employed a qualitative approach using direct observation of the ritual procession, in-depth interviews with traditional leaders, community figures, and local residents, as well as documentation studies from archives, media, and academic literature. Research instruments included observation guidelines, interview guides, and visual documentation. Data analysis techniques consisted of data reduction, data display, and thematic conclusion drawing. The findings indicate that the Bakar Tongkang tradition has undergone a harmonious process of cultural acculturation between Chinese cultural elements and local culture without eliminating its sacred values and original identity. This tradition functions not only as a religious ritual but also as a symbol of regional cultural identity, a medium for interethnic and interreligious social integration, and a driver of the local economy through tourism and small-scale enterprises. Therefore, Bakar Tongkang serves as a socio-cultural institution that reinforces tolerance, social solidarity, and cultural sustainability in a multicultural community